Violation of integrity nominally-fixed contact the by thermal breakdown. - Слащук, В.О.; Заспа, Ю.П. (Problems of Tribology, 2016)
Slashchuk V.O. Zaspa Yu.P. Violation of integrity nominally-fixed contact the by thermal breakdown. Abstract - In this work the process of thermal breakdown landing thermal conductivity. By the acoustic-emission method revealed the presence of micro disruption prior direct disruption. Defined oscillation frequency when mounting violations of integrity nominally-fixed contact. Established that the oscillation frequency of support differs from the simulated fluctuations for certain events, indicating that the hybrid nature of the oscillations. An important factor in this difference is the viscous component of the friction between the pipe thermal conductivity and its attachments. Keywords: loss of contact, acoustic emission, oscillation frequency, modeling.